How do you differentiate y=x^-2cosx-4x^-3?

1 Answer
Oct 24, 2017

dy/dx = -2x^-3cosx - x^-2sinx + 12x^-4

= (-2cosx)/x^3 - sinx/x^2 + 12/x^4

= (12-2xcosx - x^2sinx)/x^4

Explanation:

You should know a couple of rules for differentiation:

Power rule:

if f(x) = ax^n
then f'(x) = n*ax^(n-1)

Product rule:

if f(x) = g(x)h(x)
then f'(x) = g'(x)h(x) + g(x)h'(x)

And finally, summing derivatives:

d/dx(a + b) = (da)/dx + (db)/dx

Now we have the knowledge base to tackle the problem. We'll split it up.

d/dx x^-2 = -2x^-3

d/dx cosx = -sinx

so

d/dx (x^-2cosx) = -2x^-3cosx-x^-2sinx

and also

d/dx (-4x^-3) = + 12x^-4

so, in all, we have

d/dx(x^-2cosx - 4x^-3) =

-2x^-3cosx-x^-2sinx+12x^-4